Image, text and design: students' semiotic choices in nonfiction compositions. (13th May 2022) - Moses, Lindsey; Serafini, Frank
Abstract : This study investigates the ways in which first graders utilised a variety of semiotic resources when authoring nonfiction compositions during a nonfiction genre writing unit of study. Grounded in social semiotics and multimodality theories, the study uses a case study approach to explore the text, image and design resources used in students' multimodal compositions as a group followed by an in‐depth examination of two students' compositions. The data collection includes student compositions, video of classroom interactions and video recorded student composition/artefact elicitation interviews in which students discussed their composition process, authorial decision making and final composition. A multimodal approach to data analysis examines the semiotic resources used by the children, their meaning potential and purposes for inclusion in their nonfiction compositions. Findings suggest students drew upon a range of modalities, including visual images, graphic design features and movable text, in addition to written language to share their ideas and present their information through multimodal compositions. Implications include a need for curricular and instructional advancements with a greater focus on multimodal composing techniques to create inclusive spaces where students can more fully represent what they want to communicate.